Enhancing lateral flow immunoassay performance for cardiac troponin I detection with pore-size tailored silica nanoparticles and smartphone-based “AdaptiScan” analysis - Ye, Shaonian; Xu, Cifu; Li, Huilin; Feng, Shilun; Wang, Yan; Gao, Fang (Frontiers in Bioengineering and Biotechnology, 2025)
The accurate and rapid detection of cardiac troponin I (cTnI) at the point of care is crucial for the timely diagnosis of myocardial infarction (MI). This study introduces an advanced lateral flow immunoassay (LFIA) platform for cTnI detection. We employed small-sized, large-pore dendritic mesoporous silica nanoparticles (DMSN-2) to encapsulate quantum dots (QDs), achieving an enhanced QD loading capacity of 1.427 g QD/g silica, compared to 0.881 g QD/g silica for smaller pore counterparts (DMSN-1). This nano-LFIA was further integrated with “AdaptiScan”, a smartphone-based detection system that uses adaptive detection algorithms to automatically extract and analyze fluorescence signals from LFIA strips. This integration of pore-size tailored DMSNs and “AdaptiScan” resulted in a limit of detection for cTnI of 42.6 ng/L, which meets clinical diagnostic requirements. The platform offers a sensitive, cost-effective, and portable solution for rapid detection of MI, potentially transforming point-of-care testing in resource-limited settings.